Seroprevalence of hepatitis E virus infection in acute leukemia patients with allogeneic transplantation (Annals of Medical Research, 2021)
Aim: Hepatitis E Virus (HEV) infection is an emerging threat in allogeneic Hematopoietic Stem Cell Transplant (allo-HSCT) recipients. The aim of this study was to determine the prevalence of HEV infection in patients with acute leukemia before and after the transplantation.Material and Methods: The study was carried out with the serum samples taken before and after the transplantation from patients (n=42) with acute leukemia, who were 4 months to 64 years of age and who had allogenic transplant at Gazi University Hospital. All samples were tested in terms of HEV-specific anti-IgG and IgM positive value by using ELISA kit.Results: While 1 (2.3%) of the samples that were included in the study was positive anti-HEV IgG before transplantation, it was found negative after the transplantation (58th month). Positive anti-HEV IgM was not found before and after the transplantation in the collected samples. The average age of the seronegative group was determined as 30.8 ± 33.1 for male and female, respectively. There was no statistically significant difference in terms of anti-HEV IgM positivity and anti-HEV IgG positivity compared with seronegative cases of seropositive cases. Conclusions: This study was conducted to determine the prevalence of HEV infection in allogeneic stem cell patients. With this study, the incidence and importance of HEV can be determined in these patients before and after transplantation. This study can also create an important epidemiological data for our country.
Keywords: Acute Leukemia; allogeneic transplant; ELISA; Hepatitis E virus; seroprevalence